PENDAMPINGAN MASYARAKAT DALAM PERANCANGAN MEDIA BUDIDAYA MAGGOT BLACK SOLDIER FLY (BSF) UNTUK PENGOLAHAN SAMPAH RUMAH TANGGA DI KELURAHAN MARIANA, BANYUASIN - Radius Pranoto; Ricky Ravsyan Alhafez2; Hendi Warlika Sedo Putra; M. Ade Surya Pratama; Anggi Nidya Sari (Politeknik Negeri Sriwijaya, 2024)
The problem of household waste is still a problem that cannot be resolved properly and correctly. As the population increases and basic human needs increase, this will also influence the increase in the volume of waste produced. Maggot Black Soldier Fly (BSF) is known as biota that is widely used by the community in processing waste, especially household organic waste. This service activity was carried out in Mariana Village, Banyuasin Regency with the aim of; (1). increasing community awareness and skills for managing household organic waste using Maggot BSF, (2). designing media designs for cultivating Maggot BSF. The results show that training on household waste management has had a positive impact on increasing community awareness and skills regarding how to process household organic waste by utilizing the Maggot Black Soldier Fly (BSF). The resulting BSF Maggot cultivation media design is a cage design measuring 6 x 3 x 2.75 m equipped with a biopond measuring 2 x 2 x 0.8 m. Apart from that, the community has also implemented the results of this service activity by building a BSF Maggot cultivation cage and running its cultivation business